Efeito das técnicas de finalização e manipulação de resina acrílica na adesão bacteriana e rugosidade superficial - Dantas, Lucas Costa de Medeiros (2011)
The formation of biofilm and bacterial accumulation on dental materials may lead to the development of gingival inflammation and secondary caries. In dentistry different techniques can be used to make provisional restorations using acrylic polymethyl methacrylates (PMMA). The purpose of this study was to examine the effect of different surface finishing and polishing on surface roughness and the adhesion of S. sanguinis bacteria to PMMA. Fifty specimens (6mm diameter) were divided into 5 groups (n=5), following fabrication techniques and surface finishing and polishing: L (laboratorial fabrication and polishing), NF (Nealon technique and surface finishing), NP (Nealon technique and surface polishing), MF (technique recommended by manufacture and surface finishing), MP (technique recommended by manufacture and surface polishing). Five representative specimens were submitted to bacterial adhesion test and measured by counting with SEM images, two were observed the surface topography also by SEM images, other three were submitted to roughness test. Data were compared by ANOVA. The mean results of sample bacterial counts: NF: 19.6c; MP: 5.36ab; NP: 4.96ab; MF: 7.36b and L (control): 1.56a. The mean results of surface roughness: NF: 3.23d; MP: 0.52b; NP: 0.60b; MF: 2.69c and L (control): 0.07a (different letters means statistical significance difference). It was conclude that the laboratory processing of PMMA may decrease S.sanguinis adhesion and surface roughness, thus has a better prognosis in terms of periodontal health and less secondary caries.